2012
DOI: 10.1186/1471-2458-12-898
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design, methodology and sample characteristics for the Vietnam pre-conceptual micronutrient supplementation trial (PRECONCEPT): a randomized controlled study

Abstract: BackgroundLow birth weight and maternal anemia remain intractable problems in many developing countries. The adequacy of the current strategy of providing iron-folic acid (IFA) supplements only during pregnancy has been questioned given many women enter pregnancy with poor iron stores, the substantial micronutrient demand by maternal and fetal tissues, and programmatic issues related to timing and coverage of prenatal care. Weekly IFA supplementation for women of reproductive age (WRA) improves iron status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 35 publications
0
65
0
Order By: Relevance
“…Data from this study suggested that preconception health promotion messages should combine advice on preconception folic acid supplementation, correction of anaemia and correction of body weight prior to conception. These messages would also be applicable to women in other LMIC settings as similar high prevalence of undernutrition and anaemia have been reported in Vietnam and Bangladesh [9,10]. That obesity is also an emerging risk in other low income settings has been reported for women in Nepal and Bangladesh [22].…”
Section: Environmental Exposuresmentioning
confidence: 88%
See 1 more Smart Citation
“…Data from this study suggested that preconception health promotion messages should combine advice on preconception folic acid supplementation, correction of anaemia and correction of body weight prior to conception. These messages would also be applicable to women in other LMIC settings as similar high prevalence of undernutrition and anaemia have been reported in Vietnam and Bangladesh [9,10]. That obesity is also an emerging risk in other low income settings has been reported for women in Nepal and Bangladesh [22].…”
Section: Environmental Exposuresmentioning
confidence: 88%
“…The prevalence of preconception risk factors has been reported from studies, and ongoing surveillance [5][6][7][8]. Most of these reports are however from women in high income countries (HICs), where the general health status, awareness and education levels are higher than those from low and middle-income countries (LMICs) [9][10][11]. Data on risk exposures of women in low income settings are needed, as these exposures are likely to be dissimilar due to differences in socio-economic, demographic, cultural, dietary, lifestyle, environmental, regulatory and health systems characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive data on sociodemographic characteristics, including socioeconomic status, age at marriage and at random assignment, ethnicity, and education were obtained for all women at baseline (13). Detailed obstetric and health history, anthropometric measurements, and venous blood samples were also obtained at baseline and the first prenatal visit.…”
Section: Methodsmentioning
confidence: 99%
“…PRECONCEPT is a double-blind RCT with 3 treatment arms of women receiving weekly micronutrient supplements before conception. The protocol has been described in detail elsewhere (13). All eligible WRA who provided written informed consent were randomly assigned to 1 of 3 prepregnancy groups, namely, weekly supplementation of 1) MMs, 2) IFA, or 3) FA only as the control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation